The Use of Google Classroom To Improve Student’s Learning Activity Class III Students of SD Muhammadiyah Purin - Rini Setyowati (Universitas Sebelas Maret, 2020)
The purpose of this research was to improve student’s learning activity of theme 4 sub theme 1 the use of Google Classroom aplication for grade III SD Muhammadiyah Purin. Classroom Action Reseacrh methode implemented in 3 cycles which consists of: planning, implementation, observation and reflection. Technique and data collection of this reseacrh use of descriptive analysis technique of observation sheet student’s activity in the learning, score list and observation sheet. The result of this research was use of Google Classroom and Kahoot has increased of student’s activity in each cycle. In cycle I to cycle II and repeat cycle III was increased in cycle I activestudent was 12 students or 54,55%, not active students 10 students or 45,45%,in cycle 2 active students increased 20 students or 91% not active’s students 2 studentsaor 9,09% and cycle 3 wa active’s students 21 students atau 96% and not active’s students a student. The conclution that can be outcome use Google classroom aplication and Kahoot can increased student’s activity in the learning